Effect of injection the broiler hatching eggs with vitamin E and cod liver oil on some their productive traits and immune response to Newcastle disease vaccine: Mushtaq T. Abdulwahid@ and Mashaan A. Al-Zuhairy - Abdulwahid, Mushtaq T. (The Iraqi Journal of Veterinary Medicine, 2019)
Four hundred fertile eggs of broiler breeder Ross strain were incubated in commercial Hatchery. Eggs were injected into amniotic fluid on 18th day of incubation after divided into four treatment groups (100 eggs per treatment) with two replicates. First treatment was injected 100 µl of PBS, second treatment was injected with100 µl of inactivated ND vaccine, the third treatment was injected with 100 µl of inactivated ND vaccine and 50 µl vitamin E (oily form) and finally the fourth treatment was injected with 100 µl of inactivated ND vaccine and 50 µl Cod liver oil. All injected eggs were carried back into hatchery for complete hatching process. Hatched chicks were transported to the farm of the Veterinary Medicine College/University of Baghdad for 42 days from 6/10/2011 to 16/11/2011. The hatched chicks from the previously treated groups were distributed into four treatments with two replicates for up to the experimental end. Results of treated groups showed significant (P ≤ 0.05) increase in body weight, weight gain, as well as significant reduce in feed intake and improvement in feed conversion ratio, also, antibody titers against Newcastle disease virus of treated groups showed significant (P ≤ 0.05) increase progressively with age until the end of the experiment compared with broiler chicks of control.